Development of a highly sensitive noncompetitive electrochemical immunosensor for the detection of atrazine by phage anti-immunocomplex assay - González Techera, Andrés (2014)
The development of immunosensors for the detection of small molecules is of great interest because of their simplicity, high sensitivity and extended analytical range. Due to their size, small compounds cannot be simultaneously recognized by two antibodies impeding their detection by noncompetitive two-site immunoassays, which are superior to competitive ones in terms of sensitivity, kinetics, and working range. In this work, we combine the advantages of magneto-electrochemical immunosensors with the improved sensitivity and direct proportional signal of noncompetitive immunoassays to develop a new Phage Anti-Immunocomplex Electrochemical Immunosensor (PhAIEI) for the detection of the herbicide atrazine. The noncompetitive assay is based on the use of recombinant M13 phage particles bearing a peptide that specifically recognizes the immunocomplex of atrazine with an anti-atrazine monoclonal antibody. The PhAIEI performed with a limit of detection (LOD) of 0.2 pg mL−1, which is 200-fold better than the LOD obtained using the same antibody in an optimized conventional competitive ELISA, with a large increase in working range. The developed PhAIEI was successfully used to assay undiluted river water samples with no pretreatment and excellent recoveries. Apart from the first demonstration of the benefits of integrating phage anti-immunocomplex particles into electrochemical immunosensors, the extremely low and environmentally relevant detection limits of atrazine attained with the PhAIEIS may have direct applicability to fast and sensitive detection of this herbicide in the environment.